Beneficial Effects of Spore-Forming Bacillus Probiotic Bacteria Isolated From Poultry Microbiota on Broilers' Health, Growth Performance, and Immune System - Mazanko, Maria S.; Popov, Igor V.; Prazdnova, Evgeniya V.; Refeld, Aleksandr G.; Bren, Anzhelica B.; Zelenkova, Galina A.; Chistyakov, Vladimir A.; Algburi, Ammar; Weeks, Richard M.; Ermakov, Alexey M.; Chikindas, Michael L. (Frontiers in Veterinary Science, 2022)
Probiotics are known for their beneficial effects on poultry health and wellbeing. One promising strategy for discovering Bacillus probiotics is selecting strains from the microbiota of healthy chickens and subsequent screening for potential biological activity. In this study, we focused on three probiotic strains isolated from the gastrointestinal tract of chickens bred in different housing types. In addition to the previously reported poultry probiotic Bacillus subtilis KATMIRA1933, three strains with antimutagenic and antioxidant properties Bacillus subtilis KB16, Bacillus subtilis KB41, and Bacillus amyloliquefaciens KB54, were investigated. Their potential effects on broiler health, growth performance, and the immune system were evaluated in vivo. Two hundred newborn Cobb500 broiler chickens were randomly divided into five groups (n=40). Four groups received a standard diet supplemented with the studied bacilli for 42 days, and one group with no supplements was used as a control. Our data showed that all probiotics except Bacillus subtilis KATMIRA1933 colonized the intestines. Treatment with Bacillus subtilis KB54 showed a significant improvement in growth performance compared to other treated groups. When Bacillus subtilis KB41 and Bacillus amyloliquefaciens KB54 were applied, the most significant immune modulation was noticed through the promotion of IL-6 and IL-10. We concluded that Bacillus subtilis KB54 supplementation had the largest positive impact on broilers' health and growth performance.